Nonlethal Detection of Asian Fish Tapeworm in the Federally Endangered Humpback Chub Using a Molecular Screening Tool. Issue 4 (28th June 2019) - Campbell, Meredith C.; Caldwell, Colleen A.; Lewis, Teresa D.; Wilson, Wade D.; Gard, Charlotte C.
Abstract: Optimal spawning habitat of federally endangered Humpback Chub Gila cypha exists within the Little Colorado River; however, temperatures in the Little Colorado River are also ideal for proliferation of the invasive pathogenic Asian fish tapeworm Schyzocotyle acheilognathi . The current standard for positive identification of the parasite is necropsy and visual examination of the gut via microscopy, a methodology undesirable for assessing infection in endangered fishes. A swab taken at the rectum of the fish and analyzed using a novel DNA primer targeting the cestode cytochrome oxidase I subunit mtDNA gene region offers a convenient nonlethal sampling tool. To validate the nonlethal methodology, primer sensitivity (51.9%) and specificity (79.5%) were calculated by exposing captive fish to the parasite and comparing results using the lethal standard method (i.e., visual examination). Subsequently, we utilized this nonlethal methodology to address prevalence of infection and infection frequency across a range of size‐classes in a wild population of Humpback Chub and addressed possible patterns and mechanisms of infection in the Little Colorado River. When wild Humpback Chub were screened for infection prevalence in spring 2015 (21.4%, n = 140) and fall 2015 (6.6%, n = 258), the relative frequency of infection was highest in juveniles and subadult fish (200–300 mm). Elevated levels of infection near the major spawning grounds of Humpback Chub in the Little Colorado River promote parasitic infection, which may continue to persist without treatment or actions to control infections. We demonstrated that rectal swabs, in conjunction with PCR and primer‐specific identification, offer a time‐efficient nonlethal method to detect infection of Asian fish tapeworm in an endangered fish.